2020
DOI: 10.18502/jfqhc.7.4.4844
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Evaluation of Turkish Herbal Teas Before and After Infusion

Abstract: Background: Herbal teas are produced and sold in packaged or unpackaged forms all over the world. The aim of this study was microbial evaluation of Turkish herbal teas before and after infusion in boiled water. Methods: A total of 20 packaged and unpackaged samples of Turkish herbal teas, including chamomile, salvia, green, mix, apple, mate, ginger, linden, fennel, and senna tea were collected. All of the samples were analyzed before and after infusion in hot water (~100 °C). Microbiological analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It was observed that the values were within the limit values according to the acceptable microbiological limits in the "Guidelines for the Evaluation of the Quality of Herbal Medicines" of WHO and Turkish Food Codex [20,21,28]. In previous studies, it has been stated that microbial contamination of packaged products offered for sale is generally less than that of products offered for sale openly [29,34]. However, in this study, it is quite remarkable that the packaged plants contained a higher bacterial load compared to the plants sold in the open.…”
Section: Microbiological Analysis Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It was observed that the values were within the limit values according to the acceptable microbiological limits in the "Guidelines for the Evaluation of the Quality of Herbal Medicines" of WHO and Turkish Food Codex [20,21,28]. In previous studies, it has been stated that microbial contamination of packaged products offered for sale is generally less than that of products offered for sale openly [29,34]. However, in this study, it is quite remarkable that the packaged plants contained a higher bacterial load compared to the plants sold in the open.…”
Section: Microbiological Analysis Resultsmentioning
confidence: 83%
“…In none of the samples Salmonella spp. not detected [29]. Vural et al (2020) in the study of medicinal herbal teas, Escherichia coli and Salmonella spp.…”
Section: Microbiological Analysis Resultsmentioning
confidence: 98%
“…Stojanovic et al ( 2011) analysed 150 herbal teas and found 32% of the teas Cronobacter-positive [37]. Teas are part of the usual diet even of very young infants as early as the first week of life [38]. The teas are often kept over hours at the bedside of babies or patients and are used for oral hygiene or perfusion of stomach tubes [39,40].…”
Section: Microbiological Contaminants In Preterm Feedmentioning
confidence: 99%